KONTRIBUSI PEREMPUAN DALAM SEKTOR PERTANIAN PADA RUMAH TANGGA PETANI PADI DI PROVINSI ACEH - Mardiyah, Ainul; Noviar, Helmi; Ertika, Yenny; Wahyuningsih, Yayuk Eko; Ansari, Leli Putri (Agros Journal of Agriculture Science, 2024)
Since ancient times, women's involvement in maintaining the family's food needs has almost been inseparable, especially in the rice production process. This research aims to analyze the contribution of women in the agricultural sector in farming households in Aceh Province. Using quantitative descriptive methods and secondary data analysis from the Aceh Province BPS agricultural census, this research investigates the important role that women play in agriculture. The analysis was carried out using descriptive statistical methods to identify patterns of women's participation, distribution of labor based on gender, and the contribution of women in the rice farming sector of Aceh Province. Data analysis was carried out using multiple linear regression models and classical assumption tests. In this research data there is autocorrelation, therefore the author carried out data transformation using the Cochrane-Orcutt method. The research results after data transformation showed that the contribution of female agricultural workers was lower than that of male agricultural workers with a value of 18 percent. Women are actively involved in various stages of farming activities, from planting to harvest. This research also found that there were different contribution patterns between female and male workers in rice farming.